2019
DOI: 10.1002/ece3.5865
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of nematode associates with Rhynchophorus ferrugineus in southern Italy

Abstract: A survey of nematodes associated with the red palm weevil Rhynchophorus ferrugineus was conducted in southern Italy in 2015 and 2016 in order to create a species inventory and obtain data about nematode biodiversity. A total of 70 insect samples (pupae and adults) were collected from infested Phoenix canariensis, Phoenix dactylifera, and Chamaerops humilis palms in three Italian Regions: sampling took place at 11 locations in Apulia, 1 in Basilicata, and 1 in Sardinia regions. Individual insects were dissected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Rynchophorus ferrugineus completes its life cycle in palms in approximately 80 days; the pest may develop up to four broods per year, with up to 3 months of adult longevity. All the instars live associated with bacteria and other organisms [ 53 , 54 , 85 , 86 , 87 ]. The holometabolic life cycle consists of the expected sequence of egg, larvae, pupae, and adult [ 9 , 28 ] ( Table 1 ).…”
Section: Red Palm Weevilmentioning
confidence: 99%
See 2 more Smart Citations
“…Rynchophorus ferrugineus completes its life cycle in palms in approximately 80 days; the pest may develop up to four broods per year, with up to 3 months of adult longevity. All the instars live associated with bacteria and other organisms [ 53 , 54 , 85 , 86 , 87 ]. The holometabolic life cycle consists of the expected sequence of egg, larvae, pupae, and adult [ 9 , 28 ] ( Table 1 ).…”
Section: Red Palm Weevilmentioning
confidence: 99%
“…Vector insect management currently achieves the red ring disease control, but there is no efficient method for controlling the nematode once it enters the palm [ 62 ]. RPW has known symbiotic nematodes such as Mononchoides macrospiculum (Nematoda: Neodiplogastridae) and Teraorhabditis synpapillata Sudhaus, 1985 (Nematoda: Rhabditidae) with a possible role in biocontrol [ 86 , 87 ]. The palms Phoenix canariensis Hort.…”
Section: Damage To the Host Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…Baits isolated by mesh with openings of 1-mm or smaller were not colonized. In contrast, Oscheius tipulae only colonized baits making direct contact with the ground (although there is limited evidence for phoresy in O. tipulae (De Luca et al 2019)). One hypothesis is that phoretic vectors are colonizing fresh fruit and flower substrates while they are still on the plant, as is the case in some specialist species like C. inopinata (Kanzaki et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They are considered phoretic nematodes as they are normally observed on the bodies of the adults. However, recent studies have also reported the occurrence of these nematodes inside pupae and adults of red palm weevils, suggesting that they can establish other types of relationships apart from phoresy (de Luca et al., 2019 ; Troccoli et al., 2015 ). In this study, we found evidence in this context and report that Teratorhabditis synpapillata nematodes reduce lifespan of Rhynchophorus ferrugineus larvae, but not adults, suggesting then that this nematode–insect relationship is parasitic rather than only phoretic, and uncovers an important factor that regulates population dynamics of this voracious insect pest.…”
Section: Discussionmentioning
confidence: 99%